If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8/5+3z=10z-4
We move all terms to the left:
8/5+3z-(10z-4)=0
We get rid of parentheses
3z-10z+4+8/5=0
We multiply all the terms by the denominator
3z*5-10z*5+8+4*5=0
We add all the numbers together, and all the variables
3z*5-10z*5+28=0
Wy multiply elements
15z-50z+28=0
We add all the numbers together, and all the variables
-35z+28=0
We move all terms containing z to the left, all other terms to the right
-35z=-28
z=-28/-35
z=4/5
| -15x-4=-52 | | 10=(1/2)h(4+1) | | -1x=-35 | | 6t^2=294 | | 5x+2=-8+5x-2=-8 | | 18-6x=-4x-8x | | 0.4x0.04=16 | | 2x2=+3x+1 | | -1/2-(-5/9)=x | | 2(3m-2)=3m+8 | | -d+9.5=5.19-0.4d+8.69 | | -6+k=09 | | -18x-4=48 | | -5/6=2/3r | | F(5)=5x^2+10x-1 | | 2+(10+5/2n)+3n=4 | | 10-9p=-8p-10-3p | | 3(c+12)=96 | | 4,9x2-20x+24=0 | | 9+3(2-x)=3 | | 200-80x=20 | | x+2(10)=90 | | 4h+8+7h+2h=89 | | 200+m=20 | | 8x-8(2x+3)=-6(2x+5) | | 3x-20=2x-16= | | 80/200m=20 | | 200/80m=20 | | 6x-20=5x-11 | | (4x-6)+4=6x-8 | | Q=2+p | | 6x+24=7x+23 |